Kesesuaian Kebijakan Pemerintah Rusia Atas Hak-Hak Kelompok LGBT dengan Prinsip dan Standar Hak Asasi Manusia - Windy Okta Wiyanti; Cecilia Acelly Hanjani; Herbin Marulak Siahaan (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2025)
One of the human rights violations in Russia is the deprivation of rights and discrimination. As a sovereign state that ratifies international provisions in the field of human rights protection, Russia has an obligation to implement them. This research discusses the Russian Government's policy towards the rights of LGBT people in order to comply with human rights principles and standards. This research uses normative legal research methods with two approaches, namely legislation and conceptual. The results show that the Russian Government's policy towards the rights of LGBT people is not in accordance with the provisions of the UDHR and ICCPR relating to the fulfillment of human rights of citizens, because the establishment of the Anti-Gay Propaganda Law and the Russian Supreme Court Decision that includes the LGBT Movement into the Extremist group violates the principle of freedom of the UDHR and the principle of human rights protection in the ICCPR.